Нова знахідка сольпуги Galeodes araneoides Pallas, 1772 (Solifugae, Solpugidae) в Херсонській області (Україна) - Moysiyenko, I.; Radzikowski, P.; Roman, E.; Dembicz, I. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
Information on the records of common Camel Spider, Galeodes araneoides, at archaeological sites (settlements) of the Right Bank of Dnieper territory in the Kherson Region is presented: the species is recorded at one territory (Staroshvedske) based on observations of the authors (confirmed by the photo), and given for other territory (Chervonomaiatske) based on the data of survey. Last time this species was recoded on the territory of continental Ukraine more than 100 years ago.